THE INFLUENCE OF TECHNOLOGY ON ARTICLES IN TRAVEL WEBSITES - imas istiani (Indonesian Journal of Integrated English Language Teaching, 2017)
As one of the oldest genres, travel writing genre has evolved in many shapes and formats. Technology plays a great role in creating another subgenre with some differences from the printed formats. The generic features of travel writing on the internet are relatively simple in using words, only putting the key information of the described places and events, and most of the judgments are subjective evaluation. Yet, online articles provide more room for pictures that give benefits to the authors (to express their judgments), the readers (to create the image of the descriptive texts), as well as to the website traffics (for image is another tool to inquire and attract internet users). The technology also heavily influences the usage of further links and the second person pronoun “you.”